Reżim hydrologiczny rzeki Smortawy w warunkach zmiennego piętrzenia = The hydrologic regime of Smortawa river by changes of damming up - Gałka, Bernard; Ochman, Daniel; Jezierski, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
To hold back the unfavourable changes caused by defective regulation of the Smortawa river, which is the right-bank tributary of Odra river, there was built the movable weir "Hanna" on her 5+050 km. Earlier the Smortawa river wasn't controlled and it was described by a hydrological analogy to Widawa river (water-gauge Michalice). The goal of investigations is to show hydrological regime of the Smortawa river in changing piling up conditions. To reach the intentional aim authors did hydrometric measurements.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)